tp53 mutant zebrafish develop malignant peripheral nerve sheath tumors - Berghmans, Stéphane (National Academy of Sciences, 2005)
TP53 is the most frequently mutated tumor suppressor gene in human cancer, with nearly 50% of all tumors exhibiting a loss-of-function mutation. To further elucidate the genetic pathways involving TP53 and cancer, we have exploited the zebrafish, a powerful vertebrate model system that is amenable to whole-genome forward-genetic analysis and synthetic-lethal screens. Zebrafish lines harboring missense mutations in the tp53 DNA-binding domain were identified by using a target-selected mutagenesis strategy. Homozygous mutant fish from two of these lines were viable and exhibited mutations similar to those found in human cancers (tp53(N168K) and tp53(M214K)). Although homozygous tp53(N168K) mutants were temperature-sensitive and suppressed radiation-induced apoptosis only at 37°C, cells in the tp53(M214K) embryos failed to undergo apoptosis in response to γ radiation at both 28 and 37°C. Unlike wild-type control embryos, irradiated tp53(M214K) embryos also failed to up-regulate p21 and did not arrest at the G(1)/S checkpoint. Beginning at 8.5 months of age, 28% of tp53(M214K) mutant fish developed malignant peripheral nerve sheath tumors. In addition to providing a model for studying the molecular pathogenic pathways of malignant peripheral nerve sheath tumors, these mutant zebrafish lines provide a unique platform for modifier screens to identify genetic mutations or small molecules that affect tp53-related pathways, including apoptosis, cell-cycle delay, and tumor suppression.